MicroRNAs and Autoimmune-Mediated Eye Diseases - Wei, Yankai; Li, Na; Zhao, Lu; Yang, Chao; Ma, Binyun; Li, Xiaorong; Wei, Ruihua; Nian, Hong (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs (miRNAs) are evolutionarily conserved short non-coding RNAs that act at post-transcriptional regulation of gene expression by destroying target messenger RNA or inhibiting its translation. Recently, miRNAs have been identified as important regulators in autoimmunity. Aberrant expression and function of miRNAs can lead to dysfunction of immune system and mediate autoimmune disorders. Here, we summarize the roles of miRNAs that have been implicated in three representative ocular autoimmune disorders, including autoimmune uveitis, Grave’s ophthalmopathy and Sjögren’s syndrome dry eye, and discuss the potential of miRNAs as biomarkers and therapeutic targets for the diagnosis and treatment of these diseases.